Efficient Algorithm for Handling Dangling Pages Using Hypothetical Node - Singh, Ashutosh Kumar; Ravi, K.; Alex, G. (IEEE Explorer, 2010)
Dangling pages are one of the major drawbacks of page rank algorithm which is used by different search engines to calculate the page rank. The number of these pages increasing with web as the source of knowledge. However search engines are the main tools used in knowledge extraction or Information retrieval from the Web. We proposed an algorithm to handle these pages using a hypothetical node and comparing it with page rank algorithm.